2011
DOI: 10.1007/s13197-011-0338-8
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant properties and electrochemical behavior of cultivated commercial Indian edible mushrooms

Abstract: Methanolic extracts of cap and stipe of commercially obtained mushrooms Agaricus bisporus, Hypsizygus ulmarius, and Calocybe indica were analyzed for their antioxidant activity in different chemical systems including reducing power, free radical scavenging, ferric reducing antioxidant power (FRAP), superoxide scavenging, peroxide scavenging, metal chelating activities and electrochemical behavior. Scavenging effects on 2,2-diphenyl-1-picrylhydrazyl radicals were moderate (43.5-59.0%) at 1.5 mg/ml. Chelating ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
26
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 19 publications
4
26
1
1
Order By: Relevance
“…In the present study, the extracts from the cap showed higher phenolic content than the stipe, in general (Fig. 1) compared to the reported values in other mushrooms such as cap methanolic extracts for Lactarius deliciosus (10.66 ± 0.52 mg GAE/g), Tricholoma portentosum (6.57 ± 0.31 mg GAE/g) and Hypsizygus ulmarius (26.72 ± 0.50 mg GAE/g) Babu and Rao, 2013). Mushroom extracts have high levels of phenolic compounds, composed of one or more aromatic rings bearing one or more hydroxyl groups, which can exhibit extensive free radical-scavenging activities as hydrogen donors or electron-donating agents and metal ion-chelating properties.…”
Section: Total Polyphenolssupporting
confidence: 62%
See 2 more Smart Citations
“…In the present study, the extracts from the cap showed higher phenolic content than the stipe, in general (Fig. 1) compared to the reported values in other mushrooms such as cap methanolic extracts for Lactarius deliciosus (10.66 ± 0.52 mg GAE/g), Tricholoma portentosum (6.57 ± 0.31 mg GAE/g) and Hypsizygus ulmarius (26.72 ± 0.50 mg GAE/g) Babu and Rao, 2013). Mushroom extracts have high levels of phenolic compounds, composed of one or more aromatic rings bearing one or more hydroxyl groups, which can exhibit extensive free radical-scavenging activities as hydrogen donors or electron-donating agents and metal ion-chelating properties.…”
Section: Total Polyphenolssupporting
confidence: 62%
“…At 25 mg/mL concentration, the ferric reducing power of cap aqueous extract was found to be higher (332.77 ± 8.5 µM FeSO 4 equivalent) whereas, the lowest FRAP value was obtained in stipe methanolic extract at 5 mg/ml concentration (23.17 ± 0.23 µM FeSO 4 equivalent). Excellent FRAP in Hypsizygus ulmarius cap compared to other extracts were reported (Babu and Rao, 2013). The results revealed that cap aqueous extract possessed hydrogen-donating capacity indicating the significant reducing power of the extract.…”
Section: Ferric Reducing Antioxidant Power (Frap)mentioning
confidence: 87%
See 1 more Smart Citation
“…There are two basic categories of antioxidants, natural and synthetic. Recently, interest has increased considerably in finding naturally occurring antioxidants for use in foods or medicinal materials to replace synthetic antioxidants, which are being restricted due to their carcinogenicity [17,18] and mushrooms is reported that natural antioxidans [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…These reactive species take part in degenerative processes and functional changes associated with diseases like cancer, rheumatoid arthritis, cirrhosis etc (Babu & Rao, 2013).…”
Section: Introductionmentioning
confidence: 99%